THE ROLE OF INSTAGRAM SOCIAL MEDIA IN DISSEMINATING PASSPORT SERVICE INFORMATION AT THE CLASS I NON-TPI IMMIGRATION OFFICE IN BOGOR - Catur Susaningsih; Galuh Boy Hertantyo; Uwhaes Abdul Aziz (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
Social Media Instagram is one of the most widely used social media in Indonesia with a total of 61,000,000 (sixty-one million) active users and can be said to be contemporary social media. The Immigration Office Class I Non-TPI of Bogor has many social media that are used in disseminating information, however, Instagram is one of the most active media and has the highest number of followers compared to other social media. This study aims to prove the role of Instagram social media in disseminating information related to the Republic of Indonesia Travel Document Service (Passport). The method used is descriptive qualitative with data collection through interviews with related sources and by using the theory of dissemination of information conveyed by Sastropoetro, there are 4 (four) indicators, namely, must be clear, the language used is easy to reach, can cause attention, and can solve problems. Problem.